Academic Library Consortia in the United States: An Introduction - Bostick, Sharon L. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2001)
Library consortia in the United States arose from a need for sharing when resources or funding for those resources were scarce. This is as true today as it was over 100 years ago when the first American consortia were formed. Consortia continue to be a growing and important part of the library profession. This article will give an overview of academic library consortia, with special emphasis on the history and modern developments in the United States and provide a general introduction to the concept of library cooperation.